2010
DOI: 10.1111/j.1477-2574.2010.00222.x
|View full text |Cite
|
Sign up to set email alerts
|

Malignant transformation of hepatocellular adenomas into hepatocellular carcinomas: a systematic review including more than 1600 adenoma cases

Abstract: Malignant transformation of HCAs into HCCs remains a rare phenomenon with a reported frequency of 4.2%. A better selection of exactly those patients presenting with an HCA with an amplified risk of malignant degeneration is advocated in order to reduce the number of liver resections and thus reducing the operative risk for these predominantly young patients. The Bordeaux adenoma tumour markers are a promising method of identifying these high-risk adenomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
259
1
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 301 publications
(265 citation statements)
references
References 157 publications
3
259
1
2
Order By: Relevance
“…2,3,5,25 In our transplanted patients' group, lesions involved the liver in multiple sites showing smaller average diameters. A standardized nomenclature was first proposed in 1994, placing FNH in the group of regenerative nodules, as opposed to dysplastic or neoplastic nodules.…”
Section: Resultsmentioning
confidence: 99%
“…2,3,5,25 In our transplanted patients' group, lesions involved the liver in multiple sites showing smaller average diameters. A standardized nomenclature was first proposed in 1994, placing FNH in the group of regenerative nodules, as opposed to dysplastic or neoplastic nodules.…”
Section: Resultsmentioning
confidence: 99%
“…9,10 Although HCAs are benign, lesions larger than 5 cm have a relatively high risk of bleeding (25-40%) and an estimated risk of malignant transformation of approximately 5 per cent. [11][12][13] For these lesions elective resection is generally accepted as treatment of choice and can be performed both through an open or laparoscopic approach.…”
Section: Introductionmentioning
confidence: 99%
“…Malignant transformation of hca into hcc is a rare phenomenon, occurring with reported frequency of 4.2%. In a review of the available literature of hca in 2010, Stoot et al 9 identified 19 cases of malignant transformation of hca, of which only 5 occurred in men.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatocellular adenomas are uncommon benign tumours of the liver that typically occur in women taking oral contraceptive pills 9 . Malignant transformation of hca into hcc is a rare phenomenon, occurring with reported frequency of 4.2%.…”
Section: Discussionmentioning
confidence: 99%